Сучасний стан та перспективи розвитку FinTech-технологій у фінансовому середовищі України - Бондарь, Юлія Ігорівна; Bondar, Yuliia (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Об’єктом дослідження є процес формування та розвитку банківської діяльності під впливом фінансових технологій. Предметом дослідження є фінансові технології як інструмент підтримки фінансових послуг в банківській діяльності. Мета кваліфікаційної магістерської роботи полягає в узагальненні теоретичних положень, науковому обґрунтуванні щодо удосконалення та визначення основних загроз та можливостей діяльності банківського бізнесу під впливом бурхливого розвитку фінансових технологій. Одержані результати можуть бути використані для вирішення питань на рахунок впровадження FinTech-технологій у фінансовий та банківський сектор.

The object of research is the process of formation and development of banking activities under the influence of financial technologies. The subject of research is financial technologies as a tool for supporting financial services in banking. The purpose of the master's qualification work is to generalize theoretical provisions, scientifically substantiate and develop methodological approaches to improving and identifying the main threats and opportunities for banking business activities under the influence of the rapid development of financial technologies, research the global market, both banking and financial, as well as opportunities for cooperation and outlining the main trends in the development of partnership. The results obtained can be used to address issues related to the introduction of FinTech technologies into the financial and banking sectors, and to better understand the level of penetration into businesses and the population.
Current status and prospects of FinTech technology development in the financial environment of Ukraine
Науковий керівник: Баранова Валерія Вадимівна, доктор економічних наук, професор, професор кафедри банківського бізнесу та фінансових технологій
Keywords: SOCIAL SCIENCES::Business and economics; FinTech-технології; фінансовий сектор; банківський сектор; фінансове середовище; фінансовий сектор; цифрова гривня; рівень проникнення; fin-tech technologies; fin-tech sector; financial environment; financial sector; banking sector; digital UAH; penetration level